Analisis Potensi Pembangkit Listrik Tenaga Bayu dengan Turbin Angin Sumbu Vertikal di Kecamatan Sangkapura Kabupaten Gresik - Zidan Afidah; Yushardi Yushardi; Sudarti Sudarti (Jurnal Engine: Energi, Manufaktur, dan Material, 2023)
Gresik Regency's coastal Bawean Island is where Sangkapura District is situated. In 2020, there were 117,112 power consumers in the Sangkapura District. On the same island, there have been some regions without electricity daily. This demonstrates that there is still a need for electrical energy, which is growing along with the population. Additionally, growing global oil prices are a sign of the need for electrical energy. Fossil energy, which is non-renewable and can produce emissions, is the energy source that is most frequently used today. An energy crisis can be brought on by the excessive consumption of fossil fuels. The suggested remedy is to employ new renewable energy (EBT) as a source of electrical energy, taking into account that EBT is more environmentally friendly. Therefore, more study is required to determine the local potential of wind as a wind power plant (PLTB) using vertical axis wind turbines, taking into account the benefits and drawbacks of each type of turbine. The analysis of published works and the Meteorology, Climatology, and Geophysics Agency's online database is the research techniques used. According to the analysis, an average wind speed of 1.5 m/s and wind power of 10.47 watts were measured. Dim LED lights can be turned on with this amount of energy. Sangkapura District has a poor potential for wind power plants because this number is lower compared to numerous pertinent research and employs a home size. Therefore, we require a different strategy that can utilize low wind speeds to generate electricity.